China's Challenges in Moving Towards a High-Income Economy. - Song, Ligang; Zhou, Yixiao (Canberra : ANU Press, 2021)
With its per capita income surpassing US10,000, China has now drawn up ambitious plans to further lift its income to the level of developed countries. Yet various constraints need to be overcome if China is to build on the achievements of the last 40 years and further boost its growth potential.
Table 6.3 Regression results with capital and labour -- Table 6.4 Summary statistics -- Table 6.5 Industry estimation results -- Table 6.6 Industry estimation results: Process innovation -- Table 6.7 Industry estimation results: Marketing and organisational innovation -- Table 8.1 Benchmark model regression -- Table 8.2 Parallel trend test -- Table 8.3 Regression with mixed-pattern firms -- Table 8.4 Robustness test for region and industry characteristics -- Table 8.5 Robustness test for pretreatment trend and other coexistent policies -- Table 8.6 Heterogeneity test with location -- Table 8.7 Heterogeneity test regarding firm status -- Table 8.8 Heterogeneity test by region and trade mode -- Table 8.9 Heterogeneity by firm status -- Table 9.1 Currency names and their corresponding symbols -- Table 9.2 UIP regressions for the offshore renminbi against major currencies -- Table 9.3 UIP regressions for the offshore renminbi against the currencies of countries along the BRI -- Table 9.4 Augmented UIP regressions for the offshore renminbi against major currencies -- Table 9.5 Augmented UIP regressions for the offshore renminbi against the currencies of countries along the BRI -- Contributors -- Acknowledgements -- 1. Challenges and roadmaps for moving towards a high‑income economy -- 2. Tackling social challenges to avoid the middle-income trap -- 3. China's agricultural trade: A global comparative advantage perspective -- 4. China's urbanisation in the new technological revolution -- 5. Revenue-neutral tax reform in China -- 6. Innovation and its growth effects in China -- 7. Conditions in China's corporate sector -- 8. The transformation and upgrading of processing trade and its impact on firms' productivity -- 9. The renminbi's status as a safe‑haven currency -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: China--Economic conditions; Economic development; Economic development--China.; Electronic books